Effectiveness Range of Motion Therapy and Warm Water Compresses on Increasing Muscle Strength in Non-Hemorrhagic Stroke Patients: Scoping Review - Barbosa de Oliveira, Adirson; Muhith, Abdul (Chakra Brahmanda Lentera Institute, 2024)
Background: Stroke is the most common cause of disease in the world and is the highest cause of death in Indonesia, so prevention is essential to minimize disability and stroke death. To restore and increase muscle strength in stroke patients, the solution is to do Range Of Motion (ROM) Exercises and Warm Compresses. This Scoping Review aimed to identify the effectiveness of Range Of Motion therapy and warm compresses on increasing muscle strength in non-hemorrhagic stroke patients. Methods: The method used is a Scoping Review using journal databases from PubMed, Science Direct, and Google Scholar in the range of 2020-2023 with the keywords